2014
DOI: 10.5957/josr.58.4.140006
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Equations for Planing Hull Bottom Pressures

Abstract: Recently there has been increasing interest in the fluid-structure interaction problem of planing hull bottom structure during slamming events. Significant work has been done in estimating the bottom pressures that occur during a slam and incorporating this into structural models of planing craft. In this article, empirical equations for the pressure distribution on prismatic planing hulls are developed, including both hydrostatic and hydrodynamic effects, deadrise variation, trim, and wetted length. The empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…A series of non-dimensional evaluation coefficients were applied during our data process. The nondimensional pressure coefficient Cp and torque coefficient CMΔ are specified in Equations (14) and 15: As mentioned previously, the stern flaps have an obvious influence on the pressure and movement distribution. Clarifying the characteristics of stern flaps is important in the analysis of the flap action mechanism, in order to evaluate the hydrodynamic characteristics of the stern flap.…”
Section: Hydrodynamic Characteristics Of the Stern Flapmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of non-dimensional evaluation coefficients were applied during our data process. The nondimensional pressure coefficient Cp and torque coefficient CMΔ are specified in Equations (14) and 15: As mentioned previously, the stern flaps have an obvious influence on the pressure and movement distribution. Clarifying the characteristics of stern flaps is important in the analysis of the flap action mechanism, in order to evaluate the hydrodynamic characteristics of the stern flap.…”
Section: Hydrodynamic Characteristics Of the Stern Flapmentioning
confidence: 99%
“…A series of non-dimensional evaluation coefficients were applied during our data process. The non-dimensional pressure coefficient C p and torque coefficient C M∆ are specified in Equations (14) and 15:…”
Section: Hydrodynamic Characteristics Of the Stern Flapmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, P YSTAG / P N represent pressure distribution on the stagnation line. All these parameters are explained in detail by Morabito (2014). Regarding the range of applicability of these equations, the following range has been previously used by Morabito (2010) in his studies which may be considered as a suitable range of applicability.…”
Section: Hydrodynamic Pressurementioning
confidence: 99%
“…Early in 1929, Von Karman [1] firstly introduced a significant contribution on this subject. Following Karman's classic works on hull-water impact, a series of studies on the theoretical analysis of water entry problem have been reported (Wagner [2], Kapsenberg [3], Faltinsen [4][5] Morabito [6], Korobkin [7][8] and Abrate [9] et al). Due to the complexities of this problem (such as multi-physics interaction phenomenon, free surface tracking et al), only a few special cases of wedges entry water vertically at a constant velocity can be solved analytically.…”
mentioning
confidence: 99%